2015
DOI: 10.1007/s00464-015-4606-y
|View full text |Cite
|
Sign up to set email alerts
|

Are gynecologists sufficiently trained and educated on electro surgery and basic laparoscopic setting?

Abstract: Education on electro surgery and basic laparoscopic setting and laparoscopic practical training are necessary to improve and maintain laparoscopic surgical skills. The assessment of that knowledge is mandatory to define surgical competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The results of this survey are in line with the studies from Feldman [14] and Modaffari [7]. They found that only a small percentage of specialists consider themselves experts in the field of electrosurgery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this survey are in line with the studies from Feldman [14] and Modaffari [7]. They found that only a small percentage of specialists consider themselves experts in the field of electrosurgery.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies analysed the level of knowledge in surgical residents or specialists by tests and determined that clinicians are not sufficiently trained in electrosurgery [6,7,11,15]. It is often suggested that more hands-on training is necessary, while this survey shows that respondents would rather have more frequent theoretical sessions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation